Review of Harmful Algal Blooms in the Coastal Mediterranean Sea, with a Focus on Greek Waters - Christina Tsikoti; Savvas Genitsaris (Diversity, 2021)
Anthropogenic marine eutrophication has been recognized as one of the major threats to aquatic ecosystem health. In recent years, eutrophication phenomena, prompted by global warming and population increase, have stimulated the proliferation of potentially harmful algal taxa resulting in the prevalence of frequent and intense harmful algal blooms (HABs) in coastal areas. Numerous coastal areas of the Mediterranean Sea (MS) are under environmental pressures arising from human activities that are driving ecosystem degradation and resulting in the increase of the supply of nutrient inputs. In this review, we aim to present the recent situation regarding the appearance of HABs in Mediterranean coastal areas linked to anthropogenic eutrophication, to highlight the features and particularities of the MS, and to summarize the harmful phytoplankton outbreaks along the length of coastal areas of many localities. Furthermore, we focus on HABs documented in Greek coastal areas according to the causative algal species, the period of occurrence, and the induced damage in human and ecosystem health. The occurrence of eutrophication-induced HAB incidents during the past two decades is emphasized.